Penghasilan Content Creator dari Iklan Judi Online Perspektif Yusuf Al-Qharadawi - Fadillah, Tasya; Zuhri, Ahmad (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
In the development of digital technology, the phenomenon of the proliferation of online gambling advertisements by content creators through social media has emerged. This research aims to analyze the income earned by content creators from online gambling advertisements, as well as the impact of these advertisements on society from both social and economic perspectives, and Yusuf Al-Qaradawi's views on haram sources of income. The method employed is a normative legal approach with a conceptual framework. Data was collected through literature studies on the works of Yusuf Al-Qaradawi, fiqh muamalah literature, journals, theses, scientific papers, as well as field data obtained via interviews with relevant informants. The research findings indicate that although content creators do not directly engage in gambling, their role as intermediaries in disseminating sinful practices renders their income unlawful. This study recommends that content creators prioritize the halal aspect of their income sources in accordance with Islamic principles.